Capacities in Generalized Orlicz Spaces. (1st October 2018) - Baruah, Debangana; Harjulehto, Petteri; Hästö, Peter
Abstract : In this paper basic properties of both Sobolev and relative capacities are studied in generalized Orlicz spaces. The capacities are compared with each other and the Hausdorff measure. As an application, the existence of quasicontinuous representative of generalized Orlicz functions is proved.